Lumbar disc herniations - An outcome analysis of 1473 operated patients - (:unkn) unknown (SPRINGER-VERLAG WIEN, 2000)
This is a retrospective review of 1473 consecutive cases with virgin lumbar disc herniation operated on using an open conventional discectomy technique. The mean follow-up duration was 4.6 years. A single discectomy was performed in 85.1% of cases, a two-level discectomy in 14.1%, and a three-level discectomy was performed in 0.6% of cases. An additional laminotomy was performed in 7.9% of cases. Herniated disc was located at L4-5 and L5-S1 levels in 78.9% of the cases. Disc herniation was protruded and extruded in 59.7% and 40.3% of cases, respectively. Outcome analysis was perfomed using Prolo's functional and economical rating scale, and 88.1% of cases was found to be in a good condition, 8.8% in a moderate condition, and 3.1% of cases was found to be in poor condition. The most favorable outcome was observed in L5-S1 level disc herniations, and in extruded disc herniations. A good outcome in two-level disc herniations was 79.2%, and 22.2% in three level disc herniations. The overall recurrence rate was 3.7%, whereas the rate of recurrence in cases with additional laminotomy was 5.08%. It can be concluded that the best results was seen in single level disc herniations, in L5-S1 disc herniations, and in extruded disc herniations. Also it is concluded that as the number of discectomy and laminotomy increases, the rate of successful outcome decreases.
Keywords: lumbar disc herniation; outcome; DISCECTOMY; SURGERY; DISKECTOMY; SPINE; COMPLICATIONS